'Art in the Library': Interstitial readings between art education and artistic practice. Issue 1 (1st April 2014) - Juanpere, Salvador; Valera, Albert; Viladomiu, Àngels
The growing interest of many artists in alternative spaces for artistic creation and the interdisciplinary nature of most educational curricula have encouraged the teaching staff at the University of Barcelona's Faculty of Fine Arts to adopt a new methodology – an educational turn – that offers students the direct experience of creating 'artworks in the user's space'. This article reports on that experience, 'Art in the Library', which in recent years has formed part of the University's Bachelor's degree in Fine Art, in the subject Interdisciplinary Attitudes. The student artworks reported on in this paper are site-specific projects, which constitute a professional challenge for their creators and were exhibited to a general public. The authors of the paper propose that 'Art in the Library' meets a challenge in contemporary educational practice and understands art education as an act of creation.